Spesifikasi standar untuk perencanaan geometrik jalan luar kota (Rancangan akhir) - [Tidak Terdaftar] ([Tidak Terdaftar], 1990)
Spesifikasi standar untuk perencanaan geometrik jalan luar kota (Rancangan akhir)